2013
DOI: 10.1016/j.ramb.2013.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of obesity in asthma and its relations with asthma severity and control

Abstract: This study showed a high prevalence of obesity in asthmatic patients. Obese and non-obese subjects were similar in regard to asthma severity and level of asthma control. Female sex was associated with obesity in this asthma population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 31 publications
2
8
0
8
Order By: Relevance
“…Weight and height measures were used to calculate BMI (in kg/m 2 ). Overweight and obesity were defined as BMI 25.0-29.9 kg/m 2 and ≥30 kg/m 2 , respectively [ 1 ]. WC and height measures were used to calculate waist-to-height ratio (WHtR).…”
Section: Participants and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Weight and height measures were used to calculate BMI (in kg/m 2 ). Overweight and obesity were defined as BMI 25.0-29.9 kg/m 2 and ≥30 kg/m 2 , respectively [ 1 ]. WC and height measures were used to calculate waist-to-height ratio (WHtR).…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Overweight and obesity are one of the most serious public health challenges of the 21st century that pose a major risk for serious diet-related chronic diseases (i.e., cardiovascular disease, type 2 diabetes, hypertension and stroke, and certain forms of cancer), physical disabilities, musculoskeletal disorders, asthma, predisposition to some infections, and economic consequences [ 1 , 2 , 3 , 4 ]. Its prevalence has tripled in many countries in the World Health Organization (WHO) European Region since the 1980s, and the number of those affected continues to rise at an alarming rate [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Asthma exacerbations are closely tied to asthma control, and the evidence linking obesity to asthma controls is mixed, with studies supporting [32] , [33] , [34] , [35] , [36] and refuting an association. [37] , [38] , [39] A Cochrane review of weight loss interventions to improve asthma control concluded that there may be weak associations, but noted that research in this area is lacking. 40 Our failure to find an association could be confounded by our inability to assess asthma control before entry into the study.…”
Section: Discussionmentioning
confidence: 99%
“…Однако в других исследо- (5) ваниях показано, что ожирение у детей не оказывает отрицательного влияния на тяжесть бронхиальной астмы [31][32][33]; похожие результаты получены и у взрослых больных с бронхиальной астмой [34][35][36].…”
Section: результаты и обсуждениеunclassified